2014
DOI: 10.1042/bst20130227
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in the structural molecular biology of Ets transcription factors: interactions, interfaces and inhibition

Abstract: The Ets family of eukaryotic transcription factors is based around the conserved Ets DNA-binding domain. Although their DNA-binding selectivity is biochemically and structurally well characterized, structures of homodimeric and ternary complexes point to Ets domains functioning as versatile protein-interaction modules. In the present paper, we review the progress made over the last decade to elucidate the structural mechanisms involved in modulation of DNA binding and protein partner selection during dimerizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
27
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 65 publications
4
27
0
2
Order By: Relevance
“…The ETS domain of Ets‐1 has been crystallized in complex with transcription factors GABPαβ and RUNX1 . These structures, as well as homodimers of different proteins of the ETS family (Fev, Elk1, and Etv1), also show the hydrophobic patch to be shielded from the solvent through the interaction with its partners or itself. Moreover, the monomeric structure of ETS (PDB ID: 1GVJ) shows the two inhibitory domains to fold back onto this area, thus protecting the patch from any solvent exposure.…”
Section: Resultsmentioning
confidence: 99%
“…The ETS domain of Ets‐1 has been crystallized in complex with transcription factors GABPαβ and RUNX1 . These structures, as well as homodimers of different proteins of the ETS family (Fev, Elk1, and Etv1), also show the hydrophobic patch to be shielded from the solvent through the interaction with its partners or itself. Moreover, the monomeric structure of ETS (PDB ID: 1GVJ) shows the two inhibitory domains to fold back onto this area, thus protecting the patch from any solvent exposure.…”
Section: Resultsmentioning
confidence: 99%
“…5, 6, 7, 8 All ETS factors are characterized by the ETS domain, which is a highly conserved DNA-binding domain comprising ~85 amino acids that form the winged helix-turn-helix DNA-binding motif, and recognizes the core consensus DNA sequence 5′-GGA(A/T)-3′ (ETS-binding site, EBS). 9, 10 Some of them have been found to alter expression patterns involving diverse mechanisms, such as gene fusion and chromosomal rearrangements, 11, 12 amplification and/or overexpression, 13, 14 point mutations.…”
mentioning
confidence: 99%
“…For instance, Lim et al revealed co-localization with liverspecific TF-binding sites, explaining part of GR's liver cell-specific binding profiles [84]. The molecular mode of regulation at composite sites still remains to be elucidated, although it was hypothesized to fit a model in which only the co-association of the involved TFs results in productive DNA binding, as seen for classical heterodimeric TFs [85,86].…”
Section: Gr-binding Site Sequences and Gr-mediated Transrepressionmentioning
confidence: 99%